The impact of volunteering in mental health settings on nursing students' attitudes. (March 2020) - Juliá-Sanchis, Rocío; Sanjuan-Quiles, Ángela; Richart-Martínez, Miguel; Cabrero-García, Julio
Abstract: Nursing faculties are working to improve students' attitudes towards mental illness and people with severe mental illness, given the repercussions a lack of knowledge and negative attitudes may have on the quality of care. Complementing undergraduate programmes with volunteering activities affords students the opportunity to interact with people with a severe mental illness, and allow them to develop positive attitudes and overcome prejudice. Aim: to explore and deepen in nursing students attitudes prior to and following volunteering on an Acute Mental Health Inpatient Unit. By means of mixed methods approach, students were assessed at two time points by questionnaires including "Community Attitudes to Mental Illness" and "Semantic Differential", and by testimonies gathered from interviews. Positives changes in attitudes were identified and monitored over time capturing a destigmatizing tendency. The participation in educational strategies such as volunteering in Acute Mental Health Inpatient Unit, complementary to undergraduate programmes and clinical placements in mental health, allows nursing students to develop more diversified and positive attitudes towards mental illness and people with severe mental illness. The impact of an interventional education strategy is not as powerful in nursing students as it might be in students of other non-healthcare oriented university degrees due to their baseline attitudes. Highlights: The students' experience of a volunteering educational intervention was explored. Volunteering in mental health settings aids students in improving their attitudes. The students valued the opportunity to learn offered by the volunteering activity.